Peningkatan Skill Orang Tua dalam Stimulasi Kognitif, Emosional, dan Bahasa Berdasarkan Aspek Perkembangan Anak Usia Prasekolah - Harmiardillah, Sylvi; Qowi, Nurul Hikmatul; Lestari, Trijati Puspita; Wahyuni, Putri Alfiana; Azizah, Zaratul; Nisrina, Zia Fathin (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2025)
Stimulation or encouragement is really needed to maximize all the potential of preschooler-children. When parents try to provide optimal stimulation, it is important for parents to know the time and the methods to provide stimulation to children. The aim of this activity is to increase the knowledge and abilities of parents and teachers in stimulating pre-school age children, especially cognitive, social emotional and language aspects in accordance with the MBKM program in Main Performance Indicator (IKU) 3, namely lecturers doing activities outside campus and Main Performance Indicator (IKU) 2, namely Students Gain Experience outside campus. The activity is provides socialization about stimulating the growth and development of pre-school children, training on how to stimulate with flashcards, peer group mentoring and evaluation, as well as program sustainability. Based on the results of the checklist, most parents were able to demonstrate how to provide stimulation to their children, followed by an increase in the average knowledge value, namely 4.67. Parents can provide cognitive, emotional and language stimulation to maximize their child's potential and growth and development.